2005
DOI: 10.1002/pen.20329
|View full text |Cite
|
Sign up to set email alerts
|

Effects of compatibilizer and testing speed on the mechanical and morphology behaviors of co-continuous amorphous copolyester-polyoxymethylene blends

Abstract: Co-continuousamorphous copolyester (PETG)/ polyoxymethylene (POM) (50/50 wt%/wt%) blends were prepared using a twin screw extruder followed compression molding. Two types of thermoplastic polyurethane (TPU) (i.e., polyester-based and polyether-based) were used to compatibilize the blends system. The thermal properties were characterized by using differential scanning calorimetry (DSC). The mechanical properties of the co-continuous PETG/POM blends were studies through flexural and single-edge notch tensile tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…In the presence of organoclay, the segmental mobility of the polymer molecules and the plastic deformation process in the form of crazing and shear yielding are very much restricted at high deformation rates. The reduction of toughness of the materials with increasing testing speed was also reported for core‐shell rubber toughened PBT blends [23] and PETG/POM/TPU blends [24]. The increase in K IC value observed in the PA6/PP/4C‐MMT with increasing the testing speed may be attributed to the plasticizing effect caused by high content of organic modifier (octadecylamine) in the commercial organo‐MMT, i.e., 34%.…”
Section: Resultssupporting
confidence: 55%
“…In the presence of organoclay, the segmental mobility of the polymer molecules and the plastic deformation process in the form of crazing and shear yielding are very much restricted at high deformation rates. The reduction of toughness of the materials with increasing testing speed was also reported for core‐shell rubber toughened PBT blends [23] and PETG/POM/TPU blends [24]. The increase in K IC value observed in the PA6/PP/4C‐MMT with increasing the testing speed may be attributed to the plasticizing effect caused by high content of organic modifier (octadecylamine) in the commercial organo‐MMT, i.e., 34%.…”
Section: Resultssupporting
confidence: 55%
“…The cooling cycle reveals no endothermic peak, indicating that the material is completely amorphous, also proven by the absence of melting peak in the heating cycle. 22,24
Figure 6.DSC results: (a) PETGp vs. PETGf; (b) rPETGp vs. rPETGf; (c) rPETGp vs. PETGp; (d) rPETGf vs. PETGf.
…”
Section: Resultsmentioning
confidence: 99%
“…These are ideal properties for FFF printing, benefiting from high stability. 22 Kattan et al. 24 studied the difference of crystallinity between PET and PETG and found that the first can crystalize up to 40% while PETG can barely go up to 3%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tensile strength and elongation at break of pure PP are 37.79 MPa and 9%, respectively, while these values for SBS are 25.14 MPa and 687%, respectively. The tensile stress at 100% of SBS is 4.64 MPa but pure PP had no numerical value because the tensile rate is too fast for rigid PP . Tensile stress at 100% is inversely proportional to SBS content.…”
Section: Resultsmentioning
confidence: 99%